2019
DOI: 10.1093/nar/gkz692
|View full text |Cite
|
Sign up to set email alerts
|

ATP/ADP modulates gp16–pRNA conformational change in the Phi29 DNA packaging motor

Abstract: Packaging of phage phi29 genome requires the ATPase gp16 and prohead RNA (pRNA). The highly conserved pRNA forms the interface between the connector complex and gp16. Understanding how pRNA interacts with gp16 under packaging conditions can shed light on the molecular mechanism of the packaging motor. Here, we present 3D models of the pRNA–gp16 complex and its conformation change in response to ATP or ADP binding. Using a combination of crystallography, small angle X-ray scattering and chemical probing, we fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Furthermore, protein factors may also impact bcd quaternary structure. This multimerization mechanism and the ability to form more than one type of multimer is reminiscent of the bacteriophage ø29 prohead RNA (pRNA), discussed below [ 110 , 111 , 112 , 113 ] ( Figure 2 c).…”
Section: Dimerization-mediated Mrna Localizationmentioning
confidence: 99%
“…Furthermore, protein factors may also impact bcd quaternary structure. This multimerization mechanism and the ability to form more than one type of multimer is reminiscent of the bacteriophage ø29 prohead RNA (pRNA), discussed below [ 110 , 111 , 112 , 113 ] ( Figure 2 c).…”
Section: Dimerization-mediated Mrna Localizationmentioning
confidence: 99%
“…THF-II riboswitch has a relatively simple secondary structure compared to the first THF riboswitch, THF-I, which is similar to the SAM-VI riboswitch class [ 23 ]. Previous studies showed that ligand binding usually causes global conformation changes, usually involving alternative base paring, as shown by SAXS scattering and/or chemical probing data [ 45 , 46 , 47 , 48 , 49 ]. Generally, apo RNA has usually a larger Rg compared to the ligand-bound RNA.…”
Section: Discussionmentioning
confidence: 99%
“…To begin to design tRNA-antiterminator fusion for crystallization, we first sought to minimize the structure. Our starting point was the full-length antiterminator from the G. kaustophilus tRNA Gly T-box riboswitch that has been the model for most of our previous work [5,[30][31][32]49,59]. The G. kaustophilus antiterminator resembles canonical antiterminators with a proximal helix, broken by a single-stranded bulge that contains the tRNA UCCA tail recognition sequence, UGGA and a distal helix capped by a loop.…”
Section: Challenges In Crystallizing the Trna/t-box Antiterminator Co...mentioning
confidence: 99%
“…Our choice to use tRNA as a crystallization chaperone is based on prior knowledge that tRNA folds robustly strong evolutionary pressure to conserve its structure; the inspection of other tRNA crystal structures revealed strong and predictable crystal contacts and engineered tRNA fusions have shown drastically improved folding and stability when expressed in vivo [26][27][28][29]. We have previously employed tRNA fusions to determine the structure prohead RNA (pRNA) domain II structure [30,31]. We hypothesized that we could use an engineered tRNA scaffold to assist the crystallization of the usually dynamic T-box antiterminator and to potentially select tRNA acceptorantiterminator interactions in crystals.…”
Section: Introductionmentioning
confidence: 99%